THE URGENCY OF TAX AVOIDANCE MODERATED BY THE UTILIZATION OF TAX HAVENS COUNTRY - Wahyunita, Tiara; Pambudi, Januar Eky; Febrianto, Hendra Galuh (Universitas Bunda Mulia, 2024)
Background: Tax avoidance can work because there is tax planning in advance from the taxpayer. This tax planning is legal because it utilizes loopholes that are not regulated in tax regulations. If tax planning meets business needs, the results can be said to be good.Objective: The purpose of this study is to examine how the use of tax avoidance as a moderating factor impacts thin capitalization, capital intensity, and corporate social responsibility.Research Methods: This is a quantitative study that applies hypothesis testing. This study involved 26 manufacturing companies listed on the IDX from 2017 to 2021. The purposive sampling method was used to collect data. The data was tested with multiple linear regression.Research Results: Thin capitalization and capital intensity have a significant positive effect on tax avoidance, while corporate social responsibility has no effect on tax avoidance. The use of tax havens country cannot moderate the influence between thin capitalization and corporate social responsibility on tax avoidance.Originality/Wideness of Research: Using data from 2017-2021, this study investigates the relationship between thin capitalization, capital intensity, and corporate social responsibility on tax avoidance with the use of tax havens as moderation.